The Effect Of Debt Policy On The Value Of Banking Companies Listed On The Indonesian Stock Exchange - Putri, Icha Dwi; Susena , Karona Cahya (Journal of Applied Financial Management, 2025)
All companies are established with the aim of increasing the value of the firm. In an effort to increase the value of the firm,the debt can reduce the manager's desire to finance activities that are not optimal, thereby increasing the value of the firm. External conditions such as poor economic conditions can affect the company, so it will be difficult for the company to repay the loan and its interest. The higher the business risk of the company, the more cautious the company is in building its capital structure. The research object is the consumer goods industry sector listed on Indonesia Stock Exchange period 2013- 2016. This research use technique of Sampling Non Probability Sampling that is Purposive Sampling. Number of samples 28 companies or 112 units of analysis. Data analysis techniques to test each variable and hypothesis testing through a simple linear regression equation model through SPSS software Version 20. This study resu lted in the finding that debt policy has a significant positive effect on corporate value and business risk can moderate the relation of debt policy to firm value. Key words: Debt Policy, Firm Value, Business Risk,Modigliani-Miller Theory,Trade-Off Theory.